What would Europeans want a European defence union to look like? - Francesco Nicoli; Brian Burgoon; David Van der Duin (Bruegel, 2023)
While the Russian invasion of Ukraine has created a new momentum for EU defence integration, the political feasibility of such integration remains disputed, as it may entail both additional financial costs and a loss of sovereignty. Furthermore, design of defence integration is inherently multidimensional, differing in terms of scope and level, governance and sources of financing, among other dimensions. To determine the extent of public support for European security cooperation, we conducted the first conjoint experiment ever fielded on public support for alternative defence union designs. We carried out a pre-registered, randomised conjoint experiment on a highly representative sample of the French, German, Italian, Dutch and Spanish populations in November 2022. This multidimensional conjoint experiment allows us to determine the causal link between policy features of potential defence pacts, and public support or opposition to such policy. Our results show that policy packages receiving the most support require joint EU-level governance, joint purchases of military equipment through joint procurement, and repurposing of existing national expenditure as the preferred form of financing. All in all, our results show not only that there is considerable cross-border support for defence integration in Western Europe, but also that citizens in different Western European countries have generally aligned preferences regarding the actual design of such policy, indicating that a compromise policy is feasible and publicly supported. Furthermore, our results support ongoing research on the nature of European solidarity at times of crisis, suggesting that European citizens are willing to support the creation of joint institutions and policies to face issues of common concern, and therefore indicating that major crises open important windows of opportunity to re-shape EU-level policies and institutions.
Keywords: 330